2023
DOI: 10.1002/jmv.28710
|View full text |Cite
|
Sign up to set email alerts
|

ETS2 alleviates acute‐on‐chronic liver failure by suppressing excessive inflammation

Abstract: Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is a syndrome with high short-term mortality. The mechanism of the transcription factor ETS2 in ACLF remains unclear. This study aimed to clarify the molecular basis of ETS2 in ACLF pathogenesis. Peripheral blood mononuclear cells from patients with HBV-ACLF (n = 50) were subjected to RNA sequencing. Transcriptome analysis showed that ETS2 expression was significantly higher in ACLF patients than in patients with chronic liver diseases and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Michelle V. Eidt et al demonstrated that IL-18 has an accuracy in predicting fatal outcomes up to 88.9% and 90% in the severe sepsis and septic shock groups, respectively, with a sensitivity of 80% and 83% and a specificity of 100% ( Eidt et al, 2016 ). ETS2 has been recognized as an effective prognostic biomarker for patients suffering from acute-on-chronic liver failure, and it mitigates liver failure through the downregulation of the HMGB1/lipopolysaccharide-induced inflammatory response ( He et al, 2023 ). A high level of HGF is firmly associated with poor outcomes in sepsis patients ( Peng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Michelle V. Eidt et al demonstrated that IL-18 has an accuracy in predicting fatal outcomes up to 88.9% and 90% in the severe sepsis and septic shock groups, respectively, with a sensitivity of 80% and 83% and a specificity of 100% ( Eidt et al, 2016 ). ETS2 has been recognized as an effective prognostic biomarker for patients suffering from acute-on-chronic liver failure, and it mitigates liver failure through the downregulation of the HMGB1/lipopolysaccharide-induced inflammatory response ( He et al, 2023 ). A high level of HGF is firmly associated with poor outcomes in sepsis patients ( Peng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%